2016
DOI: 10.13189/ujer.2016.040915
|View full text |Cite
|
Sign up to set email alerts
|

A Pathway to Educational Accountability: The Relationship between Effective School Characteristics and Student Achievement

Abstract: The aim of this study is to determine perceptions of secondary school students towards effectiveness of their school in terms of effective school characteristics such as "Secure and Regular Environment", "High Academic Expectations", "Instructional Leadership", "Learning Opportunities", "Monitoring School Learnings" and "Positive School-Parent Relationship", and to determine the predictive power of such perceptions for student achievement (in terms of year-end academic average grade). In this study, the data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This has led to a large body of recent school effectiveness literature (e.g., Günal & Demirtasli, 2016; Mitchell et al, 2015; You, 2015). Nonetheless, the research around schools' effects on student learning dates back at least half a century.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a large body of recent school effectiveness literature (e.g., Günal & Demirtasli, 2016; Mitchell et al, 2015; You, 2015). Nonetheless, the research around schools' effects on student learning dates back at least half a century.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is seen that there are many studies that show that organizational culture affects the organizational commitment of employees (Bozoğlu, 2011;Çeliktaş, 2019;Diker, 2014;Köse, 2014;Manyas, 2018;Türkkan, 2017;Uzun, 2020). On the other hand, organizational culture (Alireisoğlu, 2020;Aslan, 2014;Balçık, 2018;Karakoç, 2019;Köse, 2014;Negis Işık, 2010;Özgenel, Canpolat, & Yağan, 2020;Özkan, 2010;Öztürk, 2015;Şimşek, 2014), organizational commitment (Ağıroğlu Bakır, 2013Demirçelik, 2017;Erceylan, 2010;Olgungül, 2017;Özgan, Külekçi, & Özkan, 2012;Özkan, 2010;Orphan, 2015), academic success (Akay, 2017;Günal, 2014;Güven, 2019;Keçeli-Kaysılı) , 2008;Otrar, 2006;Sarıer, 2016;Suna et al, 2021;Yenidunya, 2005) and school size (Akkalkan, 2009;Kalfa, 2006;Özgüler, 2014) variables are examined with different variables. However, no study has been found that considers the relationship between school culture, school engagement, school size and academic achievement together.…”
Section: School Sizementioning
confidence: 99%
“…The analysis of the stories revealed that students desire an ideal school and learning environment that prioritizes physical well-being, environmental comfort, educational and cultural well-being, socio-emotional well-being, the joy of learning, and the pursuit of dreams and innovations. Günal and Demirtasli (2016) aimed to determine the perceptions of secondary school students towards the effectiveness of their schools in terms of effective school characteristics such as "Safe and Orderly Environment", "High Academic Expectations", "Teaching Leadership", "Learning Opportunities" and they determined that high academic expectations play an important role, that there are meaningful results related to a safe and orderly environment, that teachers and students should feel safe, that the physical structure of the school is important, and that a positive school-family relationship is effective.. School and family members are important basic elements that complement each other in children's education. The child, family, and school triangle begins with the children attending school and continues for many years.…”
Section: Introductionmentioning
confidence: 99%